2004
DOI: 10.1111/j.1440-1835.2004.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of linear-oblong pyrenoids with cp-DNA along their sides in Nitzschia sigmoidea (Bacillariophyceae)

Abstract: SUMMARYIn the past 10 years Nitzschia sigmoidea (Nitzsch) W. Sm. has begun to occur in Japanese rivers in various areas. It is a common diatom in Europe but was previously absent in Japan. Each chloroplast of N. sigmoidea contains many unusual linear-oblong structures. The internal structure of the chloroplast in this species was observed using epifluorescence and electron microscopy with immunolocalization techniques. The linear-oblong structures in the chloroplasts could hardly be observed by conventional li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Furthermore, a few diatoms have no pyrenoids, and, when pyrenoids do occur, they do not always have thylakoids running through them. However, the 'membrane'(when present) around the pyrenoids could represent the ends of thylakoids (Drum 1963;Drum and Pancratz 1964;Schmid 2001;Mayama et al 2004).…”
Section: Proposals For Diatom Ccmsmentioning
confidence: 99%
“…Furthermore, a few diatoms have no pyrenoids, and, when pyrenoids do occur, they do not always have thylakoids running through them. However, the 'membrane'(when present) around the pyrenoids could represent the ends of thylakoids (Drum 1963;Drum and Pancratz 1964;Schmid 2001;Mayama et al 2004).…”
Section: Proposals For Diatom Ccmsmentioning
confidence: 99%
“…In most diatoms, the chloroplast nucleoid is arranged in a ring along the margin of the chloroplast. This includes N. vermicularis, which is Downloaded by [University of Montana] at 17:11 05 April 2015 morphologically similar to N. sigmoidea (Mayama et al 2004). These authors found that the DNA in N. sigmoidea was only detected on both sides of the linear-oblong pyrenoids and regarded this as an autapomorphic character.…”
Section: Downloaded By [University Of Montana] At 17:11 05 April 2015mentioning
confidence: 99%
“…The cells have two chloroplasts on opposite sides of the central nucleus adjacent to the girdle sides, with the bent edges of the two chloroplasts more or less overlapping (Geitler 1937). The chloroplasts have numerous elongate-rhomboidal pyrenoids scattered throughout the chloroplast (Geitler 1937, Schmid 2003, Mayama et al 2004). According to Mayama (2004), each pyrenoid is penetrated by a single thylakoid.…”
Section: Downloaded By [University Of Montana] At 17:11 05 April 2015mentioning
confidence: 99%
See 2 more Smart Citations